Penilaian Risiko Ergonomi Pada Lingkungan Kerja Perkantoran Menggunakan Metode Rapid Office Strain Assessment (ROSA) - Tangguh Pramono; Abdul Malik Sayuti; Mohammad Rizal Gaffar; Rheyna Ayu Puspitaningrum (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2022)
Computerization has entered almost all fields of work, one of which is the office workstations. The interaction of workers with computers in daily work activities cannot be avoided from various problems, one of which is the problem of employee occupational safety and health. Ergonomic hazards and risks that arise from work that requires interacting with computers are caused by workers doing repetitive work with high intensity with awkward postures and without being supported by an appropriate work environment. PT XYZ is a type of finance or financing company. All activities in the completion of work in the operational department use a computer. From the observation results, it was found that there was the use of office equipment that did not meet the rules and awkward posture of workers, and improper arrangement of the workplace. This study aims to assess the ergonomic risks that exist in the operational department with the Rapid Office Strain Assessment (ROSA) method. The ROSA method is used to measure the interaction of workers on area workstations. The assessment is divided into three sections. Section A, the interaction of workers with chairs; section B, the interaction of workers with monitors and telephones; and section C, the interaction of workers with the mouse and keyboard. The final results of the measurement will be classified in four levels: low risk, medium risk, high risk, and very high risk. The results showed that the workplace in the operational section of PT XYZ was included in the high category. The high risk of ergonomics is due to the condition of the chair that does not meet the rules of ergonomic. Keywords: Ergonomic; Rapid Office Strain Assessment (ROSA); Office Work Stations